Melacak Sejarah Perkembangan Ilmu Qirā’at dan Klasifikasinya (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The history of qirā’at development represents a long journey in shaping the recitation of the Qur’an, reflecting the intellectual richness within the Islamic tradition. In the early period, qirā’at emerged as a response to the challenges of preserving the purity and authenticity of the sacred text. Prophet Muhammad, as the recipient of revelation, implored Allah for the Qur’an to be revealed in seven different dialects, giving rise to the term “nuzila al-Qur’an ‘ala sab’ati ahrūf.” This event subsequently led to the diversity of qirāat present in society, including the existence of the seven, ten, and fourteen imams. The process of qirā’at diversity development was also influenced by geographical, social, and cultural factors, resulting in variations in pronunciation and intonation when reciting the Qur’an. In later periods, efforts towards standardization were made to avoid potential differences that could lead to conflicts. The significance of qirā’at history is evident in the preservation of this tradition through the sanad system, connecting generations of Qur’an reciters. Today, the evolution of qirā’at continues to progress, facilitated by technology that supports learning and research in this field. Therefore, a profound understanding of the history of qirā’at development not only enriches religious insights but also remains an integral part of the intellectual and cultural heritage of Islam.